Causes and Guidelines to Reduce Non-Performing Loans of Government Savings Bank, Songkhla Office Zone 2 - Suwanagarn, Chomluksana; Prommai, Pichet; Urairat, Upaporn (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2022)
This research aims 1) to study the causes of non-performing loan, 2) to compare causes of non-performing loan divided by personal factors and 3) to analyze solutions to reduce debt of NPLs for Government Savings Bank, Songkhla office zone 2. This research consisted of quantitative and qualitative data. Data was collected from 261 debtors of Government Savings Bank, Songkhla zone 2. A questionnaire was used for data collection. The data were analyzed through descriptive statistics including frequency, percentage, mean, standard deviation, and inferential statistics; one-sample t-test and one-way ANOVA. The results of the study showed that the causes of NPLs comprised of the following reasons: 1) debtors had high household expenses, 2) debtors had multiple debts and 3) debtors’ businesses struggled from lost income. Moreover, this study indicates that there was a different between education, occupation, the average of net income per month of debtors and the number of family’ members that was taken care of which effected to NPLs at 0.05 statistical significance.